THE EFFECT OF LEADERSHIP AND DISCIPLINE ON EMPLOYEE PERFORMANCE IN THE TRANSPORTATION SERVICE KAMPAR REGENCY - Monica Rafihasnah; Zamhir Basem; Azhari Azhari (Jurnal Riset Manajemen Indonesia, 2023)
This study aims to determine the effect of leadership and discipline on employee performance at the Kampar District Transportation Agency. The sample in this study were all employees at the Kampar District Transportation Agency, totaling 37 employees. The data collection techniques used were questionnaires and research files. The data analysis technique used is multiple linear regression analysis with a significant level (α) of 0.05. Simultaneously leadership and discipline have an effect on performance, based on the partial test results, discipline has an effect on performance, while leadership has no effect on employee performance. The closeness of the relationship of the independent variable to the dependent variable is very strong with the contribution of the independent variable to the fixed variable which is 95.7%.